2022
DOI: 10.1371/journal.pone.0264791
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of Hepatitis B and Hepatitis C among HIV-infected patients: A cross-sectional study from tertiary care hospital of eastern Nepal

Abstract: Introduction This study was conducted with an objective to analyze prevalence and risk factors associated with co-infection of hepatitis B virus (HBV) and hepatitis C virus (HCV) in HIV-positive patients with reference to their CD4+ T cell status. Materials and methods HIV-positive patients visiting the HIV clinic for CD4+ T cells testing at B.P. Koirala Institute of Health Sciences were tested for Hepatitis B and Hepatitis C. Data regarding age, gender, mode of HIV transmission, duration of HIV diagnosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 20 publications
3
24
1
Order By: Relevance
“…Shrestha LB et al reported 2.95% of HIV and HBV coinfected cases in their study whereas J Sarkar et al have shown a higher percentage of 8.33% HIV and HBV coinfected cases in their study. 17,18 The COVID statuses of all the Hepatitis B positive cases during the pandemic were negative. Among the 23 Hepatitis C positive cases during the pandemic, one case (4.3%) was found to be COVID positive.…”
Section: Discussionmentioning
confidence: 98%
“…Shrestha LB et al reported 2.95% of HIV and HBV coinfected cases in their study whereas J Sarkar et al have shown a higher percentage of 8.33% HIV and HBV coinfected cases in their study. 17,18 The COVID statuses of all the Hepatitis B positive cases during the pandemic were negative. Among the 23 Hepatitis C positive cases during the pandemic, one case (4.3%) was found to be COVID positive.…”
Section: Discussionmentioning
confidence: 98%
“…HCV coinfection is common among PLHIV due to their common routes of transmission. Such coinfection increases up the frequency and severity of liver disease (Shrestha & Yadav, 2022). It is reported that the co-infected patients are likely to have cirrhosis of the liver 6 times more with those compared infected solely with HCV (Fuster et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, if HIV infection is at a late stage characterized by a decreased CD4 + T cell count, the chances of co-infection with HBV and HCV are higher. 10,11 This study had some limitations. We did not count the CD4 + T cell in HIV positive samples.…”
Section: Amentioning
confidence: 93%
“…The gene sequences of recombinant proteins Pol, Env (gp41) and Gag (p24) used in this study had been codonoptimized to be expressed in Escherichia coli cells. 10,11 Pol and Env (gp41) were expressed in E. coli BL21, while Gag (p24) protein was expressed in E. coli BL21CP. Protein expression was induced using 1mM IPTG at 37°C for 4 hours.…”
Section: Expression and Purification Of Recombinant Proteinsmentioning
confidence: 99%
See 1 more Smart Citation